Perbandingan Efektivitas Kompensasi Finansial dan Non-Finansial terhadap Turnover Intention Generasi Z: Studi Literatur - Regina Suci; Agung Zulfikri (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
This study aims to analyze the comparison of the impact of financial and non-financial compensation effectiveness on turnover intention among Generation Z employees. The high turnover rates within Generation Z, despite receiving adequate financial compensation, indicate a shift in their preferences regarding the workforce. Generation Z tends to seek more than just financial compensation, such as flexibility, a supportive work environment, and opportunities for growth. The method used in this study is a literature review, analyzing various relevant scholarly journals related to strategic compensation, Generation Z characteristics, and turnover intention. The research findings show that non-financial compensation has a more significant impact in reducing turnover intention among Generation Z compared to financial compensation. Therefore, companies need to focus on aspects such as work-life balance, career development opportunities, and an inclusive and supportive work culture. These findings provide valuable insights that companies should adopt a more holistic reward approach through the total rewards concept, which includes both financial and non-financial compensation, in order to enhance loyalty and retention of Generation Z employees in the long term.